Frustration and its impact on search and rescue canines - Dickinson, Sally; Feuerbacher, Erica N. (Frontiers in Veterinary Science, 2025)
Despite advances in modern technology, dogs remain the primary detection tool in search and rescue (SAR) missions, locating missing persons across diverse and dynamic environments, including wilderness, avalanche zones, water, and disaster areas. Their exceptional olfactory abilities, combined with their capacity to process complex discrimination tasks and adapt to varied environmental stimuli, make them uniquely suited for this work. However, SAR operations can be both physically and psychologically demanding, requiring sustained focus, endurance, and consistent performance under stressful conditions. Frustration, a form of psychological stress, arises when a dog encounters blocked access to a goal or when an expectation is violated, triggering physiological and behavioral changes that may impact performance. This study investigated the physiological and behavioral responses of SAR dogs to two distinct stress conditions: psychological stress induced by frustration and physiological stress induced by moderate exercise. We measured heart rate variability as an indicator of autonomic nervous system response to stress and analyzed search task performance to assess how frustration and exercise affected the dogs' latency and accuracy in executing their trained final response to the target odor. Our results revealed significant decreases in heart rate variability following frustration and increased latency in the search task, suggesting that frustration had a more pronounced impact on the dogs' physiological state and performance compared to exercise. By examining the effects of psychological and physiological stress, this study contributes to a deeper understanding of how different stressors influence SAR dog performance and welfare. These findings provide valuable insights for optimizing training methodologies and operational preparedness, ensuring both the effectiveness and well-being of SAR dogs in the field.